Modern Slavery in the Gig Economy: Analysing the Exploitation of Gig and Freelance Workers through AI-Driven Communication Strategies and Automated Surveillance - Ioseb Gabelaia; Ramunė Bagočiūnaitė; Viktorija Navickienė (International Journal of Management, Knowledge and Learning, 2025)
Purpose: In modern corporate slavery, especially in Gig and freelance there is a significant gap concerning the critical analysis of AI-driven communication technologies and automated surveillance instruments in continued exploitation. This article aims to explore how modern communication and AI technologies contribute to modern slavery within the gig economy by focusing on understanding the mechanisms through which AI-driven communication systems and automated surveillance techniques impact the autonomy, earnings, and rights of gig and freelance workers.